Anti-Cancer Effect of Quercetin in Xenograft Models with EBV-Associated Human Gastric Carcinoma - Hwan Hee Lee; Seulki Lee; Yu Su Shin; Miyeon Cho; Hyojeung Kang; Hyosun Cho (Molecules, 2016)
Licorice extracts have been widely used in herbal and folk medications. Glycyrrhiza contains diverse range of biological compounds including triterpenes (glycyrrhizin, glycyrrhizic acid) and flavonoids (quercetin, liquiritin, liquiritigenin, glabridin, licoricidin, isoliquiritigenin). The flavonoids in licorice are known to have strong anti-cancer activities. Quercetin, the most abundant flavonoid, has been shown to have anti-ulcer, anti-cancer, antioxidant, and anti-inflammatory properties. Latent Epstein-Barr virus (EBV) infection can lead to serious malignancies, such as, Burkitt’s lymphoma, Hodgkin’s disease and gastric carcinoma(GC), and (Epstein-Barr virus associated gastric carcinoma) EBVaGC is one of the most common EBV-associated cancers. In this study, the authors first examined the anti-cancer effects of quercetin and isoliquiritigenin in vivo xenograft animal models implanted with EBV(+) human gastric carcinoma (SNU719) or EBV(−) human gastric carcinoma (MKN74), and then explored the molecular mechanisms responsible for their anti-cancer activities. The results obtained showed that anti-cancer effect of quercetin was greater than isoliquiritigenin in mice injected with EBV(+) human gastric carcinoma (SNU719) cells. On the other hand, quercetin and isoliquiritigenin had similar anti-cancer effects in mice injected with EBV(−) human gastric carcinoma (MKN74) cells. Interestingly, quercetin inhibited EBV viral protein expressions, including EBNA-1 and LMP-2 proteins in tumor tissues from mice injected with EBV(+) human gastric carcinoma. Quercetin more effectively induced p53-dependent apoptosis than isoliquiritigenin in EBV(+) human gastric carcinoma, and this induction was correlated with increased expressions of the cleaved forms of caspase-3, -9, and Parp. In EBV(−)human gastric carcinoma (MKN74), both quercetin and isoliquiritigenin induced the expressions of p53, Bax, and Puma and the cleaved forms of caspase-3 and -9 and Parp at similar levels.